Effect of phototherapy with light-emitting diodes (890 nm) on tendon repair: an experimental model in sheep - Lima de Mattos, Luiz Henrique [UNESP]; Cisneros Alvarez, Luis Emiliano [UNESP]; Miluzzi Yamada, Ana Lucia [UNESP]; Hussni, Carlos Alberto [UNESP]; Rodrigues, Celso Antonio [UNESP]; Watanabe, Marcos Jun [UNESP]; Alves, Ana Liz Garcia [UNESP] (Springer, 2015)
The effect of phototherapy with 890-nm light-emitting diodes (LEDs) on the healing of experimentally induced tendinitis in sheep was evaluated in this study. Partial tenotomies measuring 0.2 cm wide x 0.5 cm long were performed on the second third of the superficial digital flexor tendons of 10 healthy sheep. The animals were divided into two groups: "treated" (TG), treated with LEDs at the aforementioned wavelength, and "control" (CG), a control group treated with a placebo. Kinesiotherapy, which consisted of 5-min walks on grassy ground, was performed on both groups. B-mode and power Doppler ultrasonographies (US) were performed to evaluate the tendon healing process during the first 14 days after surgery and on the 21st and 28th postoperative days. Biopsies were performed on day 28 for the histopathological assessment of neovascularisation and the pattern of the tendon fibres. The absence of lameness and a significant improvement (p < 0.05) in the sensitivity to pain during palpation were observed in the treated group. Furthermore, a significant reduction in oedema and an increased number of vessels (p < 0.05) were observed in this group with the B-mode and power Doppler US, respectively. No significant difference in the evolution of the lesion was found. There was a histological difference (p < 0.05) in neovascularisation in the treated group. Phototherapy with 890-nm light-emitting diodes decreases the inflammatory process.
Keywords: Phototherapy; Tendinitis; Diodes; Physiotherapy; Laser